2009
DOI: 10.1371/journal.pcbi.1000609
|View full text |Cite
|
Sign up to set email alerts
|

Power-Law Scaling in the Brain Surface Electric Potential

Abstract: Recent studies have identified broadband phenomena in the electric potentials produced by the brain. We report the finding of power-law scaling in these signals using subdural electrocorticographic recordings from the surface of human cortex. The power spectral density (PSD) of the electric potential has the power-law form from 80 to 500 Hz. This scaling index, , is conserved across subjects, area in the cortex, and local neural activity levels. The shape of the PSD does not change with increases in local cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
824
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 692 publications
(884 citation statements)
references
References 61 publications
56
824
2
2
Order By: Relevance
“…1, 2, and 5), consistent with previous studies [Crone et al, 1998a;Leuthardt et al, 2007;Miller et al, 2007;Miller et al, 2009b]. This high frequency spectral power change has been shown to correlate directly with firing rate [Manning et al, 2009;Miller et al, 2009a;Whittingstall and Logothetis, 2009], and has been demonstrated to reflect broadspectral change across all frequencies Miller et al, 2009b]. Previous studies examined the relationship between spectral power change and BOLD change within a specific region [Logothetis et al, 2001;Maier et al, 2008;Mukamel et al, 2005;Niessing et al, 2005].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…1, 2, and 5), consistent with previous studies [Crone et al, 1998a;Leuthardt et al, 2007;Miller et al, 2007;Miller et al, 2009b]. This high frequency spectral power change has been shown to correlate directly with firing rate [Manning et al, 2009;Miller et al, 2009a;Whittingstall and Logothetis, 2009], and has been demonstrated to reflect broadspectral change across all frequencies Miller et al, 2009b]. Previous studies examined the relationship between spectral power change and BOLD change within a specific region [Logothetis et al, 2001;Maier et al, 2008;Mukamel et al, 2005;Niessing et al, 2005].…”
Section: Discussionsupporting
confidence: 84%
“…S2). A power law (constantÁf Àv ) was fit to the power spectrum from the rest period for each electrode and the power was normalized (by element-wise division at each frequency) with respect to this power law [Miller et al, 2009a]. Peaks in the normalized power spectrum, i.e., where the first derivative was 0, were detected for each electrode.…”
Section: Ecog Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The ECoG HFB power shows considerable decline in neuronal activity after the initial movement for the movement rates X1 Hz for both M1 and S1. 17 As broadband HFB power changes have been linked to neuronal population firing rate, [19][20][21] the observed decline in the ECoG HFB power at higher movement rates in this study could suggest that, after movement initiation, fewer motor cortex neurons have to fire or firing rates may possibly decline when multiple similar movements are made at a fast rate. 17 Including this subject-specific drop in neuronal activity as a weighting function in a BOLD fMRI prediction model, we obtained a close match with the measured BOLD data from the same cortical regions in the same subjects ( Figures 6A and 6B).…”
Section: Discussionmentioning
confidence: 74%
“…18 Importantly, the ECoG electrode grids employed here allowed for a spatial resolution that is on the same order as our fMRI measurements. Studies have shown that power in higher frequencies (440 Hz) correlates well with neuronal firing rates [19][20][21] and also with BOLD signal change. 22,23 The ECoG high-frequency broadband power thus provided a direct measure of electrical activity in confined neuronal ensembles, which we compared with BOLD fMRI measurements.…”
Section: Introductionmentioning
confidence: 99%